2000
DOI: 10.1034/j.1600-0609.2000.90183.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of lymphoproliferative disorders in relatives of patients withB‐cell chronic lymphocytic leukemia: relevance of the degree of familial linkage

Abstract: We assessed the familial aggregation of chronic lymphoproliferative diseases (CLD) in 3962 relatives of 169 patients with B-cell chronic lymphocytic leukemia (B-CLL). Data collection included a self-administered questionnaire. The "relative risk" considered the connection between a higher incidence of CLD and the degree of familial linkage with the probands. The model of logistic regression was statistically significant (p < 0.001), with the probability of CLD increasing in proportion to the relationship coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 8 publications
1
17
0
8
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] Similar findings have been reported for Hodgkin's lymphoma (HL) [12][13][14][15][16][17][18][19][20][21][22][23] and nonHodgkin's lymphoma (NHL). 1,9,20,22,[24][25][26][27][28][29] Populationbased studies have found CLL, HL, and NHL to co-occur in families, 1,3,5,9,20,21,[23][24][25][26][27][28][29][30][31] suggesting that shared genetic pathways may contribute to risk for multiple lymphoproliferative malignancies.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11] Similar findings have been reported for Hodgkin's lymphoma (HL) [12][13][14][15][16][17][18][19][20][21][22][23] and nonHodgkin's lymphoma (NHL). 1,9,20,22,[24][25][26][27][28][29] Populationbased studies have found CLL, HL, and NHL to co-occur in families, 1,3,5,9,20,21,[23][24][25][26][27][28][29][30][31] suggesting that shared genetic pathways may contribute to risk for multiple lymphoproliferative malignancies.…”
Section: Introductionsupporting
confidence: 73%
“…[1][2][3]5,[8][9][10] However, few studies have investigated whether having a family history of lymphoma impacts prognosis. A study based on 126 patients with CLL reported that mean survival of patients with CLL with a family history of malignancy was higher compared with patients without a family history of malignancy 55 ; however, the investigators failed to characterize malignancy type in the family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Families with what appears to be Mendelian autosomal dominant inheritance of CLL are not uncommon in the literature [Brown et al 2012a;Caporaso et al 2004;Jonsson et al 2005;Sellick et al 2006]. In fact, approximately 12% of patients with CLL report a family history of a lymphoproliferative disorder (LPD) [Brown et al 2008a], and 6-9% have a relative who also has CLL [Capalbo et al 2000;Mauro et al 2006;Yuille et al 1998]. Not surprisingly, then, the risk of developing CLL is also increased in first-degree relatives of CLL patients.…”
Section: Inherited Predisposition To Cllmentioning
confidence: 99%
“…[1][2][3][4] The detection of a CLL-associated marker in healthy relatives of patients with familial CLL may provide a surrogate marker of inherited predisposition, assisting in the identification of causative gene mutations. It is possible to identify markers of some B-cell malignancies in healthy persons, including the follicular lymphoma-associated t(14;18) translocation 5,6 and the neoplastic plasma cells common to myeloma and monoclonal gammopathy of undetermined significance (MGUS).…”
Section: Introductionmentioning
confidence: 99%